Mechanical behaviour of chicken quills and chicken feather fibres reinforced polymeric composites - (:unkn) unknown (My University, 2011)
Purpose: The objective of this study is to utilise and evaluate the mechanical properties of the chicken feather quill and fibre reinforced vinylester and polyester composites. Design/methodology/approach: Prior to production of the composites, the chicken feather fibres (CFF) were cleaned, tested and analyzed in terms of physical properties; linear density and tensile behaviour. The unidirectional CFF reinforced composites were produced with vinylester and polyester resins with three fibre reinforcement loadings (2.5, 6, 10wt%). Following experiments were conducted to determine physical properties of the control (0%) and CFF reinforced composites; tensile, flexural and Charpy impact testing. Findings: It was found that the impact properties of the CFF reinforced composites are significantly better than the control composites however both the tensile and the flexural properties of the CFF reinforced composites have poorer values compared to the control composites. For the 10% CFF reinforced vinylester composite, Charpy impact value was 4.42 kgj/mm 2 which was 25% higher than the control vinylester composites (3.31 kgj/mm 2) and also for the 10% CFF reinforced polyester (4.56 kgj/mm 2) composite had three times better impact resistance than the control composite (1.85 kgj/mm 2). Practical implications: The CFF reinforced composite have potential applications due to its improved impact behaviour. Originality/value: If the poultry waste can be utilised and used any engineering applications they will be preferred due to low-cost and superior characteristics and the most importantly they will not cause ecological and health problems. © Copyright by International OCSCO World Press.
Keywords: Chicken feather; Composites; Mechanical properties; Polyester; Vinylester